Soret and Dufour effects on mixed convection in a non-Darcy porous medium saturated with micropolar fluid - Srinivasacharya, D.; RamReddy, Ch. (Nonlinear Analysis: Modelling and Control, 2011)
In this paper, the Soret and Dufour effects on the steady, laminar mixed convection heat and mass transfer along a semi-infinite vertical plate embedded in a non-Darcy porous medium saturated with micropolar fluid are studied. The governing partial differential equations are transformed into ordinary differential equations. The local similarity solutions of the transformed dimensionless equations for the flow, microrotation, heat and mass transfer characteristics are evaluated using Keller-box method. Numerical results are presented in the form of velocity, microrotation, temperature and concentration profiles within the boundary layer for different parameters entering into the analysis. Also the effects of the pertinent parameters on the local skin friction coefficient and rates of heat and mass transfer in terms of the local Nusselt and Sherwood numbers are also discussed.